IMPLEMENTASI PEMBERIAN NAFKAH IDDAH DAN MUT’AH BERDASARKAN STRATA SOSIAL : Studi di Pengadilan Agama Kelas 1A Palu - Amelia, Friska; Hasyim, Muhammad Syarif; Mursyid, Besse Tenriabeng (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
The provision of iddah and mut'ah maintenance is the maintenance given to the wife after the legal provisions regarding the consequences of breaking up a marriage due to divorce according to the provisions of the law, among other things, the court can oblige the ex-husband to provide living costs and/or determine certain obligations for the ex-wife. The costs of living and obligations referred to in these provisions are iddah and mut'ah living. In this regard, the description in this article discusses how the provision of Iddah and mut'ah support is implemented based on social strata in the Religious Courts and the inhibiting and supporting factors for the implementation of the provision of Iddah and mut'ah support based on social strata. This article uses sociological legal research using empirical data. Data obtained through interview techniques, documentation studies, observation and data reduction, data presentation, verification and checking the validity of the data. It shows that in determining the judge's decision regarding the provision of iddah and mut'ah living based on social strata, this is when the judge wants to impose a burden on the husband in paying iddah living to the wife, in this case it does not burden the husband and does not harm the wife, with the judge's basic reference being to look at the ability from the applicant. The provision of iddah and mut'ah maintenance is based on the appropriateness and propriety of a husband's income. When the panel of judges wants to decide on the iddah and mut'ah maintenance that will be given to the wife, there is no definite calculation because basically each judge usually has a different opinion on the amount of maintenance that will be charged to the ex-husband. The provision of mut'ah maintenance is a gift of mementos in the form of money or objects by a husband to his ex-wife, except for his ex-wife qobla al dukhul and does not mean the wife who is nusyuz for providing mut'ah maintenance, the judge looks at how long they have lived together as a married couple.